Motivation, ethical dilemmas and satisfaction associated with the new performance appraisal system in the new remuneration system remuneration system among teachers in Sarawak - Speedy Bena, Anak Albert Luna. (2001)
This study is a survey to determine trained teachersʼ motivational levels, perception of the ethnical dilemmas and satisfaction levels in response to the New Performance Appraisal System (Sistem Baru Penilaian Prestasi) under the New Remuneration System (Sistem Saraan Baru) introduced by the government in 1992. The study is focused on trained secondary schools teachers (both graduate and non-graduate teachers) in Zone C in Kuching-Samarahan Division, Sarawak.